Empirisch gepflückt: Alltagsexegesen. Forschungsüberblick und methodologische Erwägungen - Schramm, Christian (Protokolle zur Bibel, 2014)
Exegetical research is currently developing a broader conception of itself (“erweitertes Selbstverständnis”, Strube); support for “empirical Bible Studies” (Dieckmann) is on the increase. Practical theology is no longer the only academic discipline dealing with current processes of the construction of meaning and understanding in Biblical texts. However, research efforts on this rather new field of exegetical studies remain largely unconnected - on the theoretical as well as on the methodical level (collection and evaluation of data). In view of the above, the present article undertakes a survey of the exegetical treatment of “everyday life exegeses” (Schramm) and presents a systematic overview. The ana-lysis of methods and findings reveals a variety of affinities. This should encourage more concerted efforts, laying the groundwork for a successful empirical turn in exegetical studies.